The story of the African Association of Nephrology (AFRAN) - Barsoum, Rashad S (African Journal of Nephrology, 2017)
The African Association of Nephrology was founded in Cairo on 28 February 1987, during the ISN-sponsored “African Kidney and Electrolytes Conference”, being hosted and co-sponsored by the Egyptian Society of Nephrology. Twenty-five physicians interested in kidney disease, from 13 African countries, constituted the core assembly that selected a steering committee composed of five members, representing the five geographical zones in Africa. The committee proposed the name the African Association of Nephrology (AFRAN), approved its logo, defined its mission, and drafted its constitution. All were ratified at the first General Assembly meeting held in London in July of the same year. The steering committee was re-elected to continue as the Executive Committee for the first cycle and mandated to set the scene for future meetings, publications and programmes. AFRAN congresses have been held regularly ever since, triennially for three cycles, then biennially with a few exceptions. Scientific meetings including Continuing Medical Education activities and hands-on workshops addressing local kidney and electrolyte disorders, have been held in most African countries, with generous logistical and financial support by the International Society of Nephrology (ISN). The abstracts of the first congress were published in Kidney International. Meeting proceedings were usually distributed by hand, thanks to representatives of pharmaceutical companies in the various African countries. A quarterly newsletter was edited and published in the Sudan, upgraded to a journal (the African Journal of Nephrology) in 1997 and self-published from Egypt until the editorial office moved to South Africa in 2012. A registry of nephrologists and dialysis units in Africa was compiled and published from Algeria in 1989, then updated in the Sudan a few years later. More recently, an African Renal Registry was established, now hosted in South Africa. Numerous fellowships were offered by the better-off countries to their emerging neighbours, being sponsored by international organizations, mainly the ISN. Joint research has been conducted mainly through these fellowships. By its 10th birthday, AFRAN had encompassed all African countries, to become the official pan-African federation of national renal societies. The ISN initiatives for supporting the developing world, originally operated under the umbrella of the Commission for the Global Advancement of Nephrology (COMGAN), were instrumental in supporting AFRAN’s foundation and sustainability. Besides the ISN, AFRAN became affiliated to many other regional and all national societies of nephrology, which qualified it to serve as the principal liaison between African nephrology and that in the rest of the world.